Determinanty oprocentowania kredytów w bankach komercyjnych (część II) - Przybylska-Kapuścińska, Wiesława (Wydział Prawa i Administracji UAM, 1997)
The article presents the impact of various macroeconomic factors on the level of interest rates applicable to credits granted by commercial banks. Specifically, the article considers the following factors: (a) inflation, (b) demand and supply of credit funds in the monetary market, (c) cost of credit guarantees and ear-marked provisions, (d) subsidies for credits granted to preferred groups of customers, (e) monetary market inter-bank interest rates, and (f) competition in the banking sector. The article also presents various difficulties and limitations faced by banks in their credit pricing polices. These difficulties and limitations result from variety of considerations which must be taken into account by these banks.
Determinants of credit interest rates in commercial banking (Part two - Macroeconomic factors)